PENGARUH POLA DIET MENGONSUMSI IKAN LAUT TERHADAP FUNGSI KOGNITIF LANSIA - Harijawan, Elizabeth Natasya (Oceana Biomedicina Journal, 2024)
BACKGROUND Along with advances in technology, economy and health, the life expectancy of the world's population tends to increase. This has an impact on increasing the number of elderly (old) population. Aging is a natural process experienced by every human being and has been going on since the beginning of life. The aging process involves various physical multidimensional changes so it is a complex process. Includes mental, social, spiritual and physical changes. Changes in this mental aspect have an impact on cognitive function decline. A number of efforts can be made to inhibit the progression of the rate of decline in cognitive function, one of which is a good diet. METHODS A study of 17 research articles from accredited and reputable international journals was conducted to study the effect of dietary patterns of consuming marine fish on the cognitive function of the elderly. RESULTS Diet pattern has an effect on the cognitive function of the elderly. The Mediterranean diet pattern, consumption of wine, nuts, fruits, vegetables, protein foods, and seafood was correlated with lower cognitive decline, while the Western diet was associated with higher cognitive decline. Dietary patterns of consuming marine fish are associated with lower levels of cognitive decline in the elderly. CONCLUSIONS Good dietary patterns, such as the Mediterranean diet and consumption of marine fish, are correlated with lower rates of cognitive decline in the elderly.